A short history of the girl next door - Reck, Jared (2017)
After years of pining for the girl next door, fifteen-year-old Matthew Wainwright must deal with Tabby dating a popular senior just when he needs her most.
Keywords: Basketball -- Fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Basketball stories; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Bildungsromans